2016
DOI: 10.1042/bsr20160035
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol ameliorates renal injury in spontaneously hypertensive rats by inhibiting renal micro-inflammation

Abstract: SynopsisMicro-inflammation plays an important role in the pathogenesis of spontaneously hypertensive rat (SHR). In the present study, we investigated the therapeutic potential of resveratrol (RSV), a polyphenol with anti-fibrosis activity in hypertensive renal damage model. In SHR renal damage model, RSV treatment blunted the increase in urine albumin excretion, urinary β 2 -microglobulin (β 2 -MG), attenuated the decrease in creatinine clearance rate (CCR). The glomerular sclerosis index (1.54 + − 0.33 compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 46 publications
(40 reference statements)
2
28
0
Order By: Relevance
“…Chronic inflammation was an important feature in the initiation and progression of hypertensive kidney disease [ 10 , 11 ]. Notably, both animal and human studies reported that elevated IL-6 expression levels contribute to the pathogenesis of chronic kidney disease in hypertension [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic inflammation was an important feature in the initiation and progression of hypertensive kidney disease [ 10 , 11 ]. Notably, both animal and human studies reported that elevated IL-6 expression levels contribute to the pathogenesis of chronic kidney disease in hypertension [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that renal cortical expression of cyclooxygenase-2 (COX-2) was upregulated in a salt -induced hypertension diet that may play a role in the pathogenesis of hypertensive renal injury [ 9 ]. This indicates that the activation of leukocytes and certain cytokines propagate a state of chronic inflammation in hypertensive nephropathy patients, which likely contributes to the progression of chronic kidney disease and end-stage renal disease [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“… 10 Inhibiting renal inflammation attenuates renal injury in SHR. 5 There seems every reason to believe that the protective role of BCL6 in attenuating the Ang II-induced HK-2 cell injury may at least partially attribute to the attenuation of NLRP3 inflammasome activation and inflammation. It is noted that BCL6 also repressed the LPS-induced upregulation of NLRP3 and mature IL-1 β in HK-2 cells, suggesting that the anti-inflammation effect of BCL6 is not limited to the Ang II-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Resveratrol ameliorates renal injury by inhibiting renal inflammation in SHR. 5 Angiotensin (Ang) II is a pro-inflammatory cytokine, which is one of the main mechanisms involved in hypertension-induced tissue damage. 6 , 7 Renal inflammation has an important role in the development of hypertension and may be a target for attenuating hypertension.…”
mentioning
confidence: 99%
“…The degree of kidney tubular interstitial injury was assessed by calculating the proportion of areas with dilatation/flattening of kidney tubules, loss of brush boundary, formation of tubular cast, tubular degeneration and vacuolation. Marking standards were scored from 0 to 4 (normal structure scores 0; ≤25% of areas injured scores 1; 26%‐50% of areas injured scores 2; 51%‐75% of areas injured scores 3; >75% of areas injured scores 4).…”
Section: Methodsmentioning
confidence: 99%